1983
DOI: 10.1073/pnas.80.10.2834
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the leukemogenic protein of avian myeloblastosis virus and of its normal cellular homologue.

Abstract: The genome of the replication-defective avian myeloblastosis virus (AMV) contains an inserted cellular sequence (amy) that is part of the oncogene responsible for acute myeloblastic leukemia in chickens infected with AMV. Three antisera raised against distinct synthetic peptides predicted from the long open reading frame of amy specifically precipitated the same 48-kilodalton protein (p48amn) from leukemic myeloblasts but not from normal hematopoietic tissue, fibroblasts, or from fibroblasts infected with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 34 publications
2
71
0
Order By: Relevance
“…In addition, an inframe termination codon occurs just 5' of the splice acceptor site for the ®rst captured exon. As a result, the 48 kDa-v-Myb protein is produced by a subgenomic spliced viral mRNA that fuses the ®rst six codons of the gag gene in-frame to 371 codons of vmyb (Boyle et al, 1983;. The 3' cellular/viral recombination event occurred within an exon of c-myb, resulting in a fusion of the last eleven codons of the env gene in-frame with v-myb.…”
Section: The Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an inframe termination codon occurs just 5' of the splice acceptor site for the ®rst captured exon. As a result, the 48 kDa-v-Myb protein is produced by a subgenomic spliced viral mRNA that fuses the ®rst six codons of the gag gene in-frame to 371 codons of vmyb (Boyle et al, 1983;. The 3' cellular/viral recombination event occurred within an exon of c-myb, resulting in a fusion of the last eleven codons of the env gene in-frame with v-myb.…”
Section: The Virusesmentioning
confidence: 99%
“…The proteins (Figure 1) The 48 kDa v-Myb protein encoded by AMV, the 135 kDa Gag-Myb-Ets protein encoded by the E26 virus, and the 75 kDa c-Myb protein are all nuclear and bind to the same DNA sequence (AACNG) (Biedenkapp et al, 1988;Boyle et al, 1983Boyle et al, , 1984Klempnauer et al, , 1984Klempnauer and Sippel, 1987). The sequence that de®nes the Myb family of proteins is an approximately 50 amino acid motif with a series of conserved residues including three tryptophans separated by a characteristic spacing (reviewed in Lipsick, 1996).…”
Section: The Virusesmentioning
confidence: 99%
“…The nucleotide sequence of v-myb represents a partial copy of a cellular gene, c-myb, and has been transduced into the viral genome from a chicken host (3,4,6,11,12). The viral gene encodes a 45,000-Mr protein, p45v-m b (1,7), which in turn is a truncated version of the 75,000-Mr protein (p75cn`yb) encoded by chicken c-myb (7). Both proteins are located in the cell nucleus (8), but the means by which p45v-,n,b elicits oncogenic transformation and the function of its cellular counterpart, p75c-l,'b, remain obscure.…”
mentioning
confidence: 99%
“…These cells expressed v-myb, the oncogene of AMV, producing a 45,000-molecular-weight protein termed p45vmY (8,21 shown previously for other cell types (2, 11) this fluorescence was nuclear. By using anti-myc serum, it was found that approximately 80% of the cells exhibited nuclear fluorescence before cloning and 90 to 100% exhibited nuclear fluorescence after cloning (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cellular genes from which the viral oncogenes v-myb and v-myc were derived have been termed c-myb and c-myc, respectively (4,9). Both c-myb and c-myc have been found to be expressed in hematopoietic cells, c-myb primarily in immature hematopoietic cells and c-myc in dividing hematopoietic cells and in a variety of other proliferating cells such as fibroblasts and B-lymphocytes (4,8,12,16,17,(20)(21)(22). In normal chicken and mouse myelomonocytic cells, the expression of both cellular genes appears to decrease as the cells become more differentiated (10,12,16,17,35,36).…”
mentioning
confidence: 99%